TEACHING THE COURSE OF SULPHIC ACID PRODUCTION IN INDUSTRY WITH THE HELP OF PEDAGOGICAL TECHNOLOGIES (Conferencea, 2023)
There are several methods of teaching using pedagogical technologies in the production of sulfuric acid in industry. The benefits of using advanced teaching methods such as e-learning platforms, virtual reality simulations and interactive multimedia content to improve the learning experience and results for students and professionals were discussed.